2004
DOI: 10.1158/1078-0432.ccr-03-0194
|View full text |Cite
|
Sign up to set email alerts
|

The Stable Nitroxide Tempol Facilitates Salivary Gland Protection during Head and Neck Irradiation in a Mouse Model

Abstract: Purpose: Radiotherapy is commonly used to treat a majority of patients with head and neck cancers. The longterm radiation-induced reduction of saliva output significantly contributes to the posttreatment morbidity experienced by these patients. The purpose of this study was to test the ability of the stable-free radical Tempol (4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl), an established radioprotector, to prevent radiation-induced salivary hypofunction in mice.Experimental Design: The heads of C3H mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 44 publications
(54 reference statements)
2
59
0
Order By: Relevance
“…This represents an average reduction in salivary flow of 58%. In our previous study (12), we found a similar reduction in salivary output after 15 Gy.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This represents an average reduction in salivary flow of 58%. In our previous study (12), we found a similar reduction in salivary output after 15 Gy.…”
Section: Resultssupporting
confidence: 77%
“…Single irradiation doses at 15 Gy were delivered to only the animal's head by a Therapax DXT300 X-ray irradiator (Pantak, Inc., East Haven, CT) using 2.0-mm Al filtration (300 kVp) at a dose rate of 1.9 Gy/min. This irradiation dose leads to significant (60%) loss of salivary flow (12). Immediately after irradiation, animals were removed from the Lucite jig and housed (five animals per cage) in a climate and light-controlled environment and allowed free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such consequence of radiotherapy is the occurrence of xerostomia, decreased saliva production, in the treated area which can result in dental caries, infection, dysphagia and significant discomfort. Since the radioprotective effects of nitroxides appear to be selective for normal tissues, the ability of Tempol to prevent damage to the salivary glands from irradiation was studied [35]. Pilocarpine-induced salivary gland output eight weeks after a single dose of radiation was compared between C3H mice treated with Tempol and controls.…”
Section: Radioprotectionmentioning
confidence: 99%
“…Tempol treatment alone significantly reduced radiation-induced salivary hypofunction in a mouse model [67].…”
Section: Therapy For Childhood Thyroid Cancermentioning
confidence: 94%